Investigations on car emissions under the urban traffic conditions with the influence on Timişoara air quality - Negoiţescu, Arina; Tokar, Adriana (Transport, 2013)
Poor air quality, a high traffic level and environmental noise as well as traffic congestion and greenhouse gases emissions require establishing measures, necessary to achieve an environmentally-friendly urban habitat. The priority areas of action in order to reduce greenhouse gases emissions are transportation and construction. Implementing sustainable urban transport plans, including specific measures to promote energy-efficient vehicles and to reduce carbon dioxide (CO2) emissions, will contribute to local reduction of greenhouse gases emissions. In order to evaluate the concentrations of car exhausted emissions under the urban traffic conditions in Timişoara, Romania, which have negative effects on the air quality, experimental researches were achieved regarding the traffic simulation with a non-EURO car operating with two fuel types (petrol and LPG). These researches were performed in the Road Vehicles Lab at the University ‘Politehnica’ of Timişoara and aimed a route in Timişoara downtown with a large agglomeration of vehicles (a traffic light intersection and a non-traffic light one, 6 pedestrian traffic light crossings and 4 non-traffic light ones). The studied route is of 2.3 kilometers length, where the traffic is carried on ‘bar to bar’ and is transited in 2588 seconds. As a result of primary pollutants recordings, the values for the engine transition operating mode are obtained which show the necessity of imposing some measures concerning traffic restrictions in agglomerate areas for these car types. The simulation results also revealed that a viable alternative for a short term to reduce the pollutants emissions which has an impact on the urban environment is to use LPG instead of petrol as a fuel for cars as the analyzed one. First Published Online: 03 Apr 2013